Commentary: The experience of depression during the careers of elite male athletes - Ringland, A. (Frontiers in Psychology, 2016)
A commentary on: The Experience of Depression during the Careers of Elite Male Athletes by Doherty, S., Hannigan, B., and Campbell, M. J. (2016). Front. Psychol. 7:1069. doi: 10.3389/fpsyg.2016.01069